Hukum Talak pada Wanita Haid Menurut Empat Imam Madzhab - Miftahul Zanah Aulia Putri; M. Kholil Nawawi; Yono Yono (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
This study examines the "LAW OF TALAK ON HAID WOMEN ACCORDING TO THE FOUR MAZHAB IMAMS". In more detail, discussing Divorce is a law that is prescribed for a couple who is no longer possible to maintain a good family relationship. This divorce opportunity can be chosen by the husband by paying attention to the procedures and procedures that are in accordance with Islamic law. There are several laws that scholars are not coherent and have different opinions, especially regarding the concept of divorce in terms of time. This study aims to examine the opinions of four madhhab priests. The problem investigated is how the views of the four madhhab priests on the legal concept of divorce for menstruating women. This study aims to analyze the views of four madhhab priests on the law of divorce for menstruating women. This research is a research that uses a normative approach with a qualitative descriptive method, which describes the views of four priests of a school of thought. The results obtained from the discussion of this study, namely that if a husband drops divorce to his wife while menstruating, it is a form of disobedience and is unlawful and this divorce is called the wife of bid'i talak, ascribed to the forbidden heresy. Therefore, it is important to explain in this thesis the views of the scholars of the four schools of thought. About the law of divorce in menstruating women. It was concluded that according to the scholars of the four schools of thought, the law of divorce for menstruating women is haram and regarding the imposition of divorce on the wife during menstruation, there are differences of opinion regarding the iddah. Keywords: divorce, the four schools of thought, menstruating women